The Role of Project LEAD in Increasing the Numbers of Minority and Female Educational Administrators - Naida Tushnet Bagenstos (Educational Considerations, 1989)
LEAD centers provide special content or sponsor separate tracks of activities to address particular needs of minorities and women. (Special Program Focuses.)